Fenomena Dominasi Perempuan Dalam Drama Korea Queen Of Tears - Jamiati KN (Mathematics Education Study Program, 2024)
Korean dramas (K-Drama) have become a significant popular culture phenomenon in representing gender issues and the role of women. This research examines the phenomenon of female dominance in the Korean drama